2018
DOI: 10.1038/nature25172
|View full text |Cite
|
Sign up to set email alerts
|

Precision editing of the gut microbiota ameliorates colitis

Abstract: Summary Inflammatory diseases of the gastrointestinal tract are frequently associated with changes in gut microbial communities that include an expansion of facultative anaerobic bacteria of the Enterobacteriaceae family (phylum Proteobacteria), a common signature of dysbiosis (1–8). Here we show that a dysbiotic expansion of Enterobacteriaceae during gut inflammation could be prevented by tungstate treatment, which selectively inhibited molybdenum cofactor-dependent microbial respiratory pathways that are onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
334
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(347 citation statements)
references
References 42 publications
12
334
0
1
Order By: Relevance
“…82 Interestingly, a recent study reported that accurate regulation of gut microbiome by using tungstate, which could specifically inhibit molybdenum-cofactor-dependent microbial respiratory pathways, relieved IBD with minimal side effects. 83 The transformation or precision editing of gut microbiome may be applied to treat T1D in the future. In humans, several clinical trials using probiotics to treat T1D are undergoing, which are summarized in Table 2.…”
Section: T1d Treatment and Gut Microbiomementioning
confidence: 99%
“…82 Interestingly, a recent study reported that accurate regulation of gut microbiome by using tungstate, which could specifically inhibit molybdenum-cofactor-dependent microbial respiratory pathways, relieved IBD with minimal side effects. 83 The transformation or precision editing of gut microbiome may be applied to treat T1D in the future. In humans, several clinical trials using probiotics to treat T1D are undergoing, which are summarized in Table 2.…”
Section: T1d Treatment and Gut Microbiomementioning
confidence: 99%
“…These organisms rely on several Moco-dependent enzymes in the anaerobic respiration to survive the hypoxic conditions of the host body (Hurdle, O’Neill, Chopra, & Lee, 2011). More recently, Moco biosynthesis in enterobacteria in gut microbiome was shown to be essential for these organisms to cause inflammation, and small molecule inhibitors of Moco biosynthesis was shown effective to prevent such inflammation (Zhu et al, 2018). …”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of the nonantibiotics currently in clinical use can alter the intestinal microbiota, and this antibiotic‐like effect needs to be taken seriously; at the same time, these findings also provide clues for the development of new antibiotics . Tungstate treatment specifically targets unique respiratory pathways in members of the Enterobacteriaceae family, which are overrepresented during intestinal inflammation, and restores gut microbiota homeostasis . As an inhibitor of α‐glucosidase, the small molecule acarbose selectively limits Bacteroides access to polysaccharides by inhibiting the starch utilization system and thus results in a loss of competitive advantage for Bacteroides in the microbial community .…”
Section: Gut Microbiota‐based Diagnosis and Therapiesmentioning
confidence: 99%